WOMEN EMPOWERMENT OF THE MAIN CHARACTER MALEFICENT MISTRESS OF EVIL (2019) - Sari Lubis, Herlina; Endang Woro Kasih, E. Ngestirosa (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2025)
The film Maleficent: Mistress of Evil (2019), is a Disney film produced apart from entertainment for the public. With the aim of uncovering the representation of women's power through qualitative descriptive approaches and feminist theories. The depiction of the characters Maleficent and Aurora is positioned as a powerful and independent symbol, to face the challenge of patriarchal power displayed through the antagonist character, Queen Ingrith. Studi ini adalah studi descriptive qualitative. As well as by describing the data obtained through scenes, images, dialogues and narratives to reveal facts in accordance with the objectivity of the research. This study employed Madsen’s theory on women empowerment and Karl Max’s marxist feminist supported by Tong’s feminist theories. The film also highlights the emotional, moral, and social complexities that women face. The results of the study show that the film Maleficent: Mistress of Evil (2019) depicts women's resistance and response to traditional norms, and offers a form of leadership based on equality and empathy. The study found out that there are some issues found in the film. They are advancing gender equality, facing social inequality and promoting systemic change for gender equality. The film highlights the importance of systemic changes in the concept of power and gender, which shows that women can also use power and leadership without having to resort to violence